Community Health Status Indicators: Adding a Geospatial Component - Janet L. Heitgerd, PhD; Andrew L. Dent, MBA, MA; James B. Holt, MPA, PhD; Kimberlee A. Elmore, PhD; Koren Melfi, MPH; Jennifer M. Stanley, MA; Keisher Highsmith, DrPH; Norma Kanarek, MPH, PhD; Karen Frederickson Comer, MLA; Marilyn M. Metzler, RN; Brian Kaplan, MS, MA (Centers for Disease Control and Prevention, 2008)
An Internet mapping application is being introduced in conjunction with the release of the second version of the Community Health Status Indicators (CHSI) Report. The CHSI Geographic Information Systems (GIS) Analyst is an easy-to-use Web-based mapping application that provides new opportunities for the visualization, exploration, and understanding of the indicators. Indicators can be mapped and compared visually to other areas, including peer counties and neighboring counties. The Web site is accessible from a link on the CHSI Report Web site or directly from an Internet Web browser. In this paper, we discuss the conceptualization and implementation of this public health mapping application.